Ethnopharmacology in Ireland: an overview - DE SOUSA MENEZES, FABIO (My University, 2014)
The aim of this review was to extract information of the book Medicinal Plants in Folk Tradition: An Ethnobotany of Britain & Ireland published in 2004 by Allen and Hatfield, to give an overview of plants with medicinal potential and their applications. This study attempts to attest, observe and comment on the diversity of plants, as well as the accompanying information which inevitably is vital for the future development of herbal medicines for human therapy. Initially, the information in relation to medicinal plants in Ireland only was extracted from the above-mentioned book and organised in tables. Afterwards, it was analysed through the construction of maps and the positioning of each piece of information in specific geographical regions of the country. Its division into provinces was taken into consideration as well as into counties within the provinces. These maps and graphs illustrate the most predominantly reported botanical families identified and utilised (Asteraceae, Scrophulariaceae and Lamiaceae), and to the most frequently cited medicinal uses were attributed to topical applications. As a result we can see that the uses of traditional medicines vary among these different geographical areas of the country. Not only different uses were reported but also different plants used to treat the same condition, or different conditions treated with the same plant depending on the county. Various phytopharmaceuticals date back several decades and despite the existing evolving technology, without a doubt herbal medicines can and still do provide exceptional and efficacious outcomes like many of the conventional remedies available today.
PUBLISHED
Keywords: Ethnopharmacology; Ireland; Asteraceae; Scrophulariaceae; Lamiaceae